Induced‐Fit Mechanism in Class I Terpene Cyclases1. Issue 29 (30th May 2014) - Baer, Philipp; Rabe, Patrick; Fischer, Katrin; Citron, Christian A.; Klapschinski, Tim A.; Groll, Michael; Dickschat, Jeroen S.
Abstract We present crystallographic and functional data of selina‐4(15), 7(11)‐diene synthase (SdS) from Streptomyces pristinaespiralis in its open and closed (ligand‐bound) conformation. We could identify an induced‐fit mechanism by elucidating a rearrangement of the G1/2 helix‐break motif upon substrate binding. This rearrangement highlights a novel effector triad comprising the pyrophosphate sensor Arg178, the linker Asp181, and the effector Gly182‐O. This structural motif is strictly conserved in class I terpene cyclases from bacteria, fungi, and plants, including epi‐isozizaene synthase (3KB9), aristolochene synthase (4KUX), bornyl diphosphate synthase (1N20), limonene synthase (2ONG), 5‐epi‐aristolochene synthase (5EAT), and taxa‐4(5), 11(12)‐diene synthase (3P5R). An elaborate structure‐based mutagenesis in combination with analysis of the distinct product spectra confirmed the mechanistic models of carbocation formation and stabilization in SdS.